(untitled) (Jurnal Teknodik, 2018)
The reseach was conducted in SDN Mekar Jaya, East Depok. The purpose of this reseach is to find out the correlation between nutritional knowledge and food habit. Data were collected from one Primary School, 150 SD students and parents were selected randomly. Data were analyzed by Pearson correlation and Distribution Freuency. The result of this study shows that there is a positive Correlation between nutrition knowledge and food habits.